Cartographies policières : la dimension vernaculaire du contrôle territorial - Melina Germes (EchoGéo)
Crime mapping in police work is subject to many controversies, which underestimate two important elements. First, the anteriority of mapping practices within the police before the implementation of crime mapping technologies. Secondly, mapping practices in the police are often self-taught i.e. without proper cartographical education. Thus, police mapping practices have to be unterstood as a particular professionnal culture, and should be distinguished from the expertise of professionnal cartographers. This paper highlights the vernacular dimension of police cartographic work and shows how the multiple police cartographies serve a territorial project aimed at control. Thanks to a field research about cartography in the french Gendarmerie Nationale, the paper contributes to a police geography rooted in international critical cartography and francophone geography.